2009
DOI: 10.1677/joe-09-0020
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term effects of maternal nicotine exposure during lactation on body adiposity, lipid profile, and thyroid function of rat offspring

Abstract: Epidemiological studies show a higher prevalence of obesity in children from smoking mothers and smoking may affect human thyroid function. To evaluate the mechanism of smoking as an imprinting factor for these dysfunctions, we evaluated the programing effects of maternal nicotine (NIC) exposure during lactation. Two days after birth, osmotic minipumps were implanted in lactating rats, divided into: NIC (6 mg/kg per day s.c.) for 14 days; Control -saline. All the significant data were P!0 . 05 or less. Body we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
79
3
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(103 citation statements)
references
References 87 publications
14
79
3
7
Order By: Relevance
“…This kind of dissociation between fat mass and leptinemia was already reported in other models (Toste et al 2006, Rodrigues et al 2009). Although we cannot draw a direct comparison between the models of nicotine exposure and ETS exposure, Oliveira et al (2009) observed higher adiposity and hyperleptinemia in pups from nicotine-treated dams on lactation, while in the present study, we found lower body fat in S pups, which can be associated with other cigarette components or substances conveyed through the milk, since S offspring had no direct contact with cigarette smoke.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…This kind of dissociation between fat mass and leptinemia was already reported in other models (Toste et al 2006, Rodrigues et al 2009). Although we cannot draw a direct comparison between the models of nicotine exposure and ETS exposure, Oliveira et al (2009) observed higher adiposity and hyperleptinemia in pups from nicotine-treated dams on lactation, while in the present study, we found lower body fat in S pups, which can be associated with other cigarette components or substances conveyed through the milk, since S offspring had no direct contact with cigarette smoke.…”
Section: Discussioncontrasting
confidence: 81%
“…In the present study, S pups did not display changes of thyroid hormone levels. Previously, we demonstrated that neonate pups from-nicotine treated dams presented primary hypothyroidism (Oliveira et al 2009). It is interesting to note that in the two models, the serum levels of cotinine detected in the progeny, although low, are similar as well as the period of exposure.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Rodent studies of tobacco smoke exposure only during lactation demonstrate increased adiposity (9). Furthermore, rodent studies of maternal nicotine, one of the many compounds found in tobacco smoke, demonstrate increased obesity in adult offspring when exposed during gestation or lactation (10)(11)(12). One potential mechanism through which MTS and maternal nicotine may program increased visceral adiposity includes alteration of glucocorticoid action on adipocytes.…”
mentioning
confidence: 99%